Effect of Phlebodium Decumanum on muscle damage, inflammation and cortisol during a precompetitive mesocycle in a National Volleyball Team - Juan José García Verazaluce; Rafael Guisado-Barrilao; Elizabeth Llera Figueroa; Germán Hernández-Cruz; Blanca R. Rangel-Colmenero; Francisco M. Ocaña-Peinado; José Raúl Hoyos-Flores; Daniel Jerez-Mayorga; Isabel María Guisado-Requena (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2023)
The severe training load of a competitive mesocycle may not be assimilated correctly by athletes, and can provoke endocrine imbalance, muscle damage and inflammation. Supplementation with antioxidants such as Phlebodium Decumanum (PHL) helps protect against such imbalances. The aim of this study is to analyse the effect of PHL on the fatigue during a precompetitive mesocycle in volleyball players. Twenty-four male volleyball players were divided into two groups (experimental and control). The experimental group was supplemented with three PHL capsules in the morning and three in the afternoon for 20 days. Blood samples were taken before training, at the end of the third week and at the end of the fourth week to evaluate creatine kinase (CK), interleukin 6 (IL-6), tumour necrosis factor-alpha (TNF-α), interleukin 10 (IL-10) and cortisol. The results show the control group, the third Cortisol were significantly increased (p < .05). In the experimental group, however, a significant increase (p < .05) was only observed in the third IL-10 value. In addition, significant differences (p < .05) were observed between the control and experimental groups in the second CK. Furthermore, there were moderate variations (effect size, ES > 0.5; 90% CI) in CK, IL-6 and TNF-α. In conclusion, PHL supplementation during a precompetitive mesocycle by volleyball players protects against the muscle damage, inflammatory modulation and cortisol response caused by fatigue.